Prognostic implications of epicardial fat volume quantification in acute pericarditis - Lazaros, G; Antonopoulos, A; Oikonomou, E; Vasileiou, P; Oikonomou, E; Stroumpouli, E; Karavidas, A; Antoniades, C; Tousoulis, D (Wiley, 2016)
The pathophysiology of acute pericarditis remains largely unknown, and biomarkers are needed to identify patients susceptible to complications. As adipose tissue has a pivotal role in cardiovascular disease pathogenesis, we hypothesized that quantification of epicardial fat volume (EFV) provides prognostic information in patients with acute pericarditis.Fifty (n = 50) patients with first diagnosis of acute pericarditis were enrolled in this study. Patients underwent a cardiac computerized tomography (CT) scan to quantify EFV on a dedicated workstation. Patients were followed up in hospital for atrial fibrillation (AF) development and up to 18 months for the composite clinical endpoint of development of constrictive, recurrent or incessant pericarditis or poor response to nonsteroidal anti-inflammatory drugs.Patients presenting with chest pain had lower EFV vs. patients without chest pain (167·2 ± 21·7 vs. 105·1 ± 11·1 cm3 , respectively, P < 0·01); EFV (but not body mass index) was strongly positively correlated with pericardial effusion size (r = 0·395, P = 0·007) and associated with in-hospital AF. At follow-up, patients that reached the composite clinical endpoint had lower EFV (P < 0·05). After adjustment for age, EFV was associated with lower odds ratio for the composite clinical endpoint point of poor response to NSAIDs or the development of constrictive, recurrent or incessant pericarditis during follow-up (per 20 cm3 increase in EFV: OR = 0·802 [0·656-0·981], P < 0·05).We report for the first time a significant association of EFV with the clinical features and the outcome of patients with acute pericarditis. Measurement of EFV by CT may have important prognostic implications in these patients.